2019
DOI: 10.1002/stco.201900008
|View full text |Cite
|
Sign up to set email alerts
|

Tension‐shear interaction of high‐strength bolts during and after fire

Abstract: Connections in steel structures play an essential role in the structural stability of the entire construction. This is also true in the event of a fire. The difficulty in designing connections for fire lies in the fact that not only material properties, but also loads applied to the connections change depending on temperature. In addition, the temperature‐dependent decrease in the tensile strength of high‐strength bolts does not coincide with the decrease in shear strength. So far, the influence of combined te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Relative strength between mating threads [7,10] Friction between mating threads Implicitly included in the reported studies but there is no clear conclusion Galvanization [7,13,18] Lubrication No studies reported Pretension Fan et al [8] Effect of washers No studies reported Applied load (static or dynamic) All reported studies adopted low strain rate except [7] exploited high strain rate of 0.02min −1 .…”
Section: Number Of Threads In the Gripmentioning
confidence: 99%
See 4 more Smart Citations
“…Relative strength between mating threads [7,10] Friction between mating threads Implicitly included in the reported studies but there is no clear conclusion Galvanization [7,13,18] Lubrication No studies reported Pretension Fan et al [8] Effect of washers No studies reported Applied load (static or dynamic) All reported studies adopted low strain rate except [7] exploited high strain rate of 0.02min −1 .…”
Section: Number Of Threads In the Gripmentioning
confidence: 99%
“…Combined stress Only one study [18] Temper temperature level Implicitly included in the reported studies but there is no clear conclusion Chemical compositions Implicitly included in the reported studies but there is no clear conclusion [22], British [27] and Japan [28] standards…”
Section: Number Of Threads In the Gripmentioning
confidence: 99%
See 3 more Smart Citations